Identificação e análise do vocabulário acadêmico em língua inglesa presente em textos acadêmico-científicos - Silva, Eduardo Batista da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Reading and writing of scientific articles and reference works in the English language rely on the knowledge of the academic vocabulary - a terminological set which shows high frequency and regular distribution in eight specialized areas (Formal and Earth Sciences, Life Sciences, Engineering, Health Sciences, Agricultural Sciences, Applied Social Sciences, Humanities, Linguistics, Language Arts and Arts), sorted in 69 subfields. The present study has the general objective of describing and analyzing the academic vocabulary in the English language, occurring in eight fields of knowledge Regarding the specific objectives, the research intends to: 1) constitute a specialized corpus in the English language; 2) propose a methodology to identify and retrieve the academic vocabulary; 3) identify the fundamental academic vocabulary; 4) establish equivalence in the Portuguese language; 5) develop a terminological dictionary of the fundamental academic vocabulary in the English language with equivalents in the Portuguese language and 6) revise the Academic Word List and the Academic Vocabulary List. To ground the theoretical framework, this research resorts to the works carried out in the realm of Terminology (BARBOSA, 1999, 2009; BARROS, 2004; CABRÉ, 1993, 1999), Corpus Linguistics (BERBER SARDINHA, 2004; SINCLAIR, 2004) and Lexical Statistics (LARSON; FARBER, 2012; OAKES, 1998; BUTLER, 1985). Concerning the methodology, we constituted an academic corpus in the English language with 113.337.773 tokens. As for the aid of software, WordSmith Tools, version 5, was the linguistic-statistical tool used to process the corpora and retrieve the terms. In order to identify the terms, we used the use coefficient (result of the multiplication of the Juilland's dispersion coefficient by the normalized frequency) and posterior validation of the eligible terms by experts. The dictionary entries were developed with 10 fields. The results allow to highlight

A leitura e a redação de artigos científicos e obras de referência em língua inglesa dependem do conhecimento do vocabulário acadêmico - um conjunto terminológico que apresenta uma alta frequência e uma distribuição regular em oito grandes áreas do conhecimento (Ciências Exatas e da Terra, Ciências Biológicas, Engenharias, Ciências da Saúde, Ciências Agrárias, Ciências Sociais Aplicadas, Ciências Humanas e Linguística, Letras e Artes), subdivididas em 69 subáreas. O presente trabalho tem o objetivo geral de descrever e analisar o vocabulário acadêmico na língua inglesa. Com relação aos objetivos específicos, a pesquisa pretende: 1) constituir um corpus de especialidade em língua inglesa; 2) propor uma metodologia para a identificação e coleta do vocabulário acadêmico; 3) identificar o vocabulário acadêmico fundamental; 4) estabelecer equivalências em língua portuguesa; 5) desenvolver um dicionário terminológico do vocabulário acadêmico fundamental em língua inglesa com equivalentes em língua portuguesa e 6) revisar a Academic Word List e a Academic Vocabulary List. Para embasar a fundamentação teórica, essa pesquisa recorrerá fundamentalmente aos trabalhos desenvolvidos no âmbito da Terminologia (BARBOSA, 1999, 2009; BARROS, 2004; CABRÉ, 1993, 1999), da Linguística de Corpus (BERBER SARDINHA, 2004; SINCLAIR, 2004) e da Estatística Lexical (LARSON; FARBER, 2012; OAKES, 1998; BUTLER, 1985). Com relação à metodologia, constituímos um corpus acadêmico em língua inglesa com 113.337.773 de tokens. No tocante ao auxílio de software, a ferramenta linguístico-estatística utilizada para processar os corpora e coletar os termos foi o WordSmith Tools, versão 5. Para identificar os termos, utilizamos o coeficiente de uso (resultado da multiplicação do coeficiente de dispersão de Juilland pela frequência normalizada) e a posterior validação dos candidatos a termo por especialistas...
Keywords: Linguistica aplicada; Lexicologia; Língua inglesa - Escrita; Comunicação na ciência - Terminologia; Linguística de corpus; Applied linguistics